PENGEMBANGAN FLIPBOOK BERBASIS AUGMENTED REALITY PADA MATERI PENINGGALAN KESULTANAN PALEMBANG DARUSSALAMPADA PESERTA DIDIK DI SMA NEGERI 10 PALEMBANG - Putri Wulandari; Muhammad Reza Pahlevi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is entitled "Development of Augmented Reality (AR) Based Flipbook on the Material of Palembang Darussalam Sultanate Heritage in SMA Negeri 10 Palembang." The purpose of this research is to develop AR-based Flipbook learning media that is valid, practical, and able to increase students' motivation and understanding in learning history. The type of research used is research and development (Research and Development) with the Alessi & Trollip model which includes the planning, design, and development stages. The assessment of the validity of AR Flipbook was obtained through expert validation results, namely material experts of 4.6 (very valid) and media experts of 4.6 (very valid). Furthermore, in the trial stage (beta test), the teacher's response reached 100% with a very practical category, while the response of class X.3 students as many as 37 people obtained a percentage of 94% (very practical), and class X.5 as many as 35 people obtained a percentage of 93.5% (very practical). Overall, the response rate reached an average of 93.9%, categorized as very practical. These results indicate that the AR-based Flipbook developed is valid, practical, and suitable for use as a history learning medium. This medium is able to attract student interest and facilitate understanding of the legacy of the Palembang Darussalam Sultanate.